2015 IEEE 12th International Symposium on Biomedical Imaging (ISBI) 2015
DOI: 10.1109/isbi.2015.7163871
|View full text |Cite
|
Sign up to set email alerts
|

Chest pathology detection using deep learning with non-medical training

Abstract: In this work, we examine the strength of deep learning approaches for pathology detection in chest radiographs. Convolutional neural networks (CNN) deep architecture classification approaches have gained popularity due to their ability to learn mid and high level image representations. We explore the ability of CNN learned from a non-medical dataset to identify different types of pathologies in chest x-rays. We tested our algorithm on a 433 image dataset. The best performance was achieved using CNN and GIST fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
178
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(180 citation statements)
references
References 12 publications
(19 reference statements)
0
178
1
1
Order By: Relevance
“…Bar et al 25 and Anavi et al 26 demonstrated the effectiveness of CNN-extracted features in characterizing chest x-rays, but did not provide comparison with traditional CADx methods as we report here. More specifically, Bar et al compared CNN-extracted features with general image descriptors such as GIST instead of CADx-specific features.…”
Section: Discussionmentioning
confidence: 69%
“…Bar et al 25 and Anavi et al 26 demonstrated the effectiveness of CNN-extracted features in characterizing chest x-rays, but did not provide comparison with traditional CADx methods as we report here. More specifically, Bar et al compared CNN-extracted features with general image descriptors such as GIST instead of CADx-specific features.…”
Section: Discussionmentioning
confidence: 69%
“…Kumar et al [8] proposed a CAD system which uses deep features extracted from an autoencoder to classify lung nodules as either malignant or benign on LIDC database. In [9], Yaniv et al presented a system for medical application of chest pathology detection in x-rays which uses convolutional neural networks that are learned from a non-medical archive. that work showed a combination of deep learning (Decaf) and PiCodes features achieves the best performance.…”
Section: Methodsmentioning
confidence: 99%
“…This means that our classifier will not be able to correctly classify images in which cancerous nodules are located at the edge of the lung. To filter noise and include voxels from the edges, we use Marker-driven watershed segmentation, as described in Al-Tarawneh et al [9]. An original 2D CT slice of a sample patient is given in Figure 7.…”
Section: Watershedmentioning
confidence: 99%
“…The network was originally trained on natural images form the ImageNet competition and the network weight are available through caffe model zoo. Several medical imaging application has either used these trained weights as a feature extractor or to initialise there network [2]. This practice is called transfer learning and it helps overcome the problem of limited training data.…”
Section: Network Architecturementioning
confidence: 99%